Mechanisms for phenotypic variation in Lesch–Nyhan disease and its variants - Sampat, Radhika (2010)
Lesch–Nyhan disease is a neurogenetic disorder caused by mutation of the HPRT1 gene on the X chromosome. There is significant variation in the clinical phenotype, with more than 300 different known mutations. There are few studies that have addressed whether similar mutations result in similar phenotypes across different patients because hypoxanthine–guanine phosphoribosyltransferase (HGprt) deficiency is rare, and most mutations are unique or limited to individual families. However, recent studies have revealed multiple unrelated patients with similar mutations, providing an opportunity to examine genotype–phenotype correlations. We found significant variation among the clinical features of 10 patients from 8 unrelated families all carrying a mutation replacing guanine with adenine at base position 143 (c.143G>A) in the HPRT1 gene. This mutation results in replacement of arginine by histidine at amino acid position 48 (p.arg48his) in the HGprt enzyme. Biochemically, the enzyme exhibits reduced thermal integrity, a mechanism that may explain clinical variation. The literature reveals similar clinical variation among other patients with similar mutations, although the variation is relatively minor across the whole population of patients. Identifiable sources of clinical variation include known limitations of clinical ascertainment and mechanisms that affect residual enzyme activity and stability. These results are helpful for understanding genotype–phenotype correlations and discordance and likely are applicable to other neurogenetic disorders where similar variation occurs.